2020
DOI: 10.3390/molecules25163572
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Biological Analysis of Highly Porous PEEK Bionanocomposites Incorporated with Carbon and Hydroxyapatite Nanoparticles for Biological Applications

Abstract: Bone regeneration for replacing and repairing damaged and defective bones in the human body has attracted much attention over the last decade. In this research, highly porous polyetheretherketone (PEEK)/hydroxyapatite (HA) bionanocomposite scaffolds reinforced with carbon fiber (CF) and carbon nanotubes (CNTs) were fabricated, and their structural, mechanical, and biological properties were studied in detail. Salt porogen (200–500 µm size) leaching methods were adapted to produce porous PEEK structures with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…Also, few articles have been published on PEEK bioactivity. Interesting observations were shared by [ 32 ], who indicated that no single apatite crystals were formed on the surface of PEEK samples for 28 days. At the same time, the EDS analysis showed a decreasing trend for the content of Ca and P, which was also shown in the studies presented in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Also, few articles have been published on PEEK bioactivity. Interesting observations were shared by [ 32 ], who indicated that no single apatite crystals were formed on the surface of PEEK samples for 28 days. At the same time, the EDS analysis showed a decreasing trend for the content of Ca and P, which was also shown in the studies presented in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations are currently being performed to develop polymer–ceramic scaffolds containing hydroxyapatite that may fill the bone defect and form conditions adequate for bone repair. Studies on the development of bone scaffolds consisting of carbon-based nanomaterials, hydroxyapatite and polyetheretherketone (PEEK) were described by Swaminathan et al They proved that the developed bionanocomposites showed high porosity, non-toxicity and good cell viability [ 18 ]. In turn, scaffolds containing non-organic silica, chitosan and hydroxyapatite were obtained and characterized by Adamski and Siuta.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques have been applied to develop porous structures on the PEEK surface, including sulfonation, melt extrusion, porogen templating, and PIII technique (Zhao et al, 2013 ; Lu et al, 2014 ; Evans et al, 2015 ; Torstrick et al, 2016 ; Hieda et al, 2017 ; Yabutsuka et al, 2017 ; Deng L.-J. et al, 2018 ; Wu et al, 2018 ; Yuan et al, 2018 ; Conrad and Roeder, 2020 ; Swaminathan et al, 2020 ; Wan et al, 2020 ). Cell viability evaluations revealed that the optimal sulfonation treatment time was 5 min (Ma R. et al, 2020 ).…”
Section: Modifications Inspired By the Topography Of Bonementioning
confidence: 99%
“…To reinforce the interfacial bonding between HA and PEEK, graphene oxide (GO) can be employed as an interfacial phase (Peng et al, 2017 ). Furthermore, the addition of graphene nanosheets, CNTs, or CF can boost the mechanical properties of PEEK/HA scaffolds (Shuai et al, 2016 ; Uddin et al, 2019 ; Swaminathan et al, 2020 ).…”
Section: Modifications Inspired By the Topography Of Bonementioning
confidence: 99%